2014
DOI: 10.1080/10643389.2013.790748
|View full text |Cite
|
Sign up to set email alerts
|

Factors and Trends Affecting the Identification of a Reliable Biomarker for Diesel Exhaust Exposure

Abstract: The monitoring of human exposures to diesel exhaust continues to be a vexing problem for specialists seeking information on the potential health effects of this ubiquitous combustion product. Exposure biomarkers have yielded a potential solution to this problem by providing a direct measure of an individual's contact with key components in the exhaust stream. Spurred by the advent of new, highly sensitive, analytical methods capable of detecting substances at very low levels, there have been numerous attempts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 253 publications
0
7
0
Order By: Relevance
“…Additionally, NPAHs in ambient air are either from primary emissions or from secondary formations. Laboratory studies and field observations have shown that 2-NP and 2-NFR are formed during the photochemical transformation of emitted PYR and FR by atmospheric oxidants [ 57 , 58 , 59 ], while 1-NP is emitted from vehicle exhausts [ 60 , 61 ]. When the concentration ratio of [2-NFR]/[2-NP] is approximately 10, 2-NP and 2-NFR are from the photochemical by the hydroxyl radical pathways, whereas when the [2-NFR]/[2-NP] concentration ratios are approximately 100, 2-NP and 2-NFR are from the reaction for gas-phase nitrate radical reactions [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, NPAHs in ambient air are either from primary emissions or from secondary formations. Laboratory studies and field observations have shown that 2-NP and 2-NFR are formed during the photochemical transformation of emitted PYR and FR by atmospheric oxidants [ 57 , 58 , 59 ], while 1-NP is emitted from vehicle exhausts [ 60 , 61 ]. When the concentration ratio of [2-NFR]/[2-NP] is approximately 10, 2-NP and 2-NFR are from the photochemical by the hydroxyl radical pathways, whereas when the [2-NFR]/[2-NP] concentration ratios are approximately 100, 2-NP and 2-NFR are from the reaction for gas-phase nitrate radical reactions [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…1-OHP is a biomarker of polycyclic aromatic hydrocarbon (PAH) exposure [6]. More than 130 studies used 1-OHP as a biomarker of PAH exposure in the workplace [5]. The correlation between 1-OHP in this study was still unclear.…”
Section: Discussionmentioning
confidence: 80%
“…Our study indicated that 2-AFLU was associated with long-term exposure estimates, but the half-life of APAHs might be short. Referring to the previous study, for biomarker concentration measurements, short-term controlled exposure and occupational settings are often more controlled and uniform than the community environment. For the long-term community environmental exposure, participants are exposed to a variety of sources including cigarette smoking, wooding burning, and dietary intake .…”
Section: Discussionmentioning
confidence: 99%